Effects of a comprehensive cardiac rehabilitation program on the quality of life of patients with cardio-vascular diseases - Samaneh Mostafavi; Marziyeh Saeidi; Hosein Heidari (Vesnu Publications, 2012)
Introduction: Health- related quality of life (HRQOL) is an important factor to evaluate the effects of different interventions on cardiovascular diseases. Improvement in HRQOL is an important goal for individuals participating in cardiac rehabilitation (CR) programs. In Iran, however, published data are lacking in this regard. The purpose of this study is assessing the impact of cardiac rehabilitation (CR) on HRQOL in patients with coronary artery disease (CAD). Materials and Methods: In this queasy-experimental study the files of 100 patients with coronary artery disease (CAD) who were referred to rehabilitation department of Isfahan cardiovascular research center were studied using a randomized sampling method. Demographic data, height, weight and waist circumference were measured. To determine the risk of the disease and designing exercise program, all patients performed an exercise test so that their echocardiography, exercise capacity and ejection fraction were defined before cardiac rehabilitation (CR). Exercise intensity was obtained based on 60 - 80 percent of maximum heart rate during the exercise test. A validated questionnaire called Short-Form 36 Health Status Survey (SF-36) was applied by a trained person to evaluate HRQOL. Cardiac rehabilitation (CR) consisted of 24 sessions each of which included a warm-up, aerobics, a cool-down and relaxation as well as 8 sessions to educate risk factor modification under supervision of rehabilitation team. Finally all the exams were repeated and data was analyzed based on sex and age groups (≥ 65 and < 65 years) using SPSS12 at level of P < 0.05 via independent t test. To compare the quality of life (QOL) score before initiation and after termination cardiac rehabilitation (CR), paired t-test was used. Results: After cardiac rehabilitation (CR) program, scores of all physical domains of the SF-36 including physical problems, role limitations due to physical problems, vitality and bodily pain improved significantly (P < 0.05) compared to the baseline data. There was not any difference between age groups (≥ 65 and < 65 years) but women had significantly greater improvement regarding physical problems and mental health (P < 0.05). Conclusion: These results indicate that cardiac rehabilitation (CR) improves the quality of life (QOL) in cardiac patients, especially in women. It was also noted that elderly patients can gain same benefits as other patients. Keywords: Quality of life, Cardiac rehabilitation, Cardiac patient